Industrial air quality and ventilation : controlling dust emissions - Logachev, Ivan Nikolaevich; Logachev, Konstantin Ivanovich, 1968- (CRC Press, 2014)
"This book presents theoretical and practical guidance for the design and implementation of local exhaust and ventilation systems in industrial facilities. It explains the mechanism and processes of ejecting airflows in different variations--from uniform air motion processes in closed chutes to the creation of accelerated air streams in a free-particle flow. It also examines the engineering methods of calculating the amount of aspirated air for various industries, and compares the calculated volumes of aspiration with real life test results"--